Model of vegetable freshness perception using luminance cues (2015)
Freshness perception is a quality discrimination process that influences our consumer choice and eating behavior, especially of highly perishable products such as vegetables. Previous research used photographic stimuli to investigate the relationship between luminance distribution and freshness perception for a cabbage leaf (C. Arce-Lopera, Masuda, Kimura, et al., 2013) and a strawberry (Carlos Arce-Lopera, Masuda, Kimura, Wada, & Okajima, 2012). In this study, the luminance and chromatic information of the freshness degradation process of four different vegetables (cabbage, strawberry, carrot and spinach) was recorded in a temperature, humidity and light controlled environment. However, instead of a camera, a 2D luminance and chromaticity analyzer (TOPCON UA1000) was chosen as the measurement equipment.